Analisis Dampak Minimarket Ritel Modern Terhadap Pasar Tradisional Menurut Perspektif Ekonomi Islam di Desa Suka Maju Jati Agung Lampung Selatan - Nur Yuliani; Lutfi Hery Rahmawan; Ana Santika (Sharing: Journal of Islamic Economics Management and Business, 2024)
This exploration plans to break down the effect of current retail minimarkets on conventional business sectors from an Islamic monetary point of view in Suka Maju Jati Agung Town, South Lampung. The sort of examination involved is quantitative exploration involving information from research perceptions as surveys and meetings with respondents. Then, at that point, the scientist completed an alternate test utilizing the SPSS 25 information handling application. In view of the aftereffects of the speculation test that has been completed, the accompanying ends can be drawn: In light of the by and large unique experimental outcomes, the Asymp esteem was gotten. signature. in the deals turnover variable, in particular (0.000) < (0.05) so Ho is dismissed so it very well may be reasoned that there is a huge contrast in turnover in conventional slows down when the presence of Alfamart and Indomaret minimarkets. In the mean time, in the general contrast test results, the Asymp esteem. signature. in the variable number of purchasers, to be specific (0.000) < (0.05), then Ho is dismissed so it very well may be reasoned that there is a huge distinction in the quantity of purchasers of customary slows down when the presence of Alfamart and Indomaret minimarkets. As per a Sharia Financial survey of the effect of Alfamart and Indomaret minimarkets on deals turnover and number of purchasers, conventional slow down organizations are not as per sharia business contest in light of the fact that the Alfamart minimarkets on Suka Maju are extremely close.